Pentostatin for treatment of steroid-refractory acute GVHD: a retrospective single-center analysis - Schmitt, Thomas; Luft, Thomas; Hegenbart, Ute; Tran, Thuong Hien; Ho, Anthony Dick; Dreger, Peter (Bone marrow transplantation, 2011)
Acute GVHD (aGVHD) remains a major cause of mortality in patients undergoing allo-SCT. In particular, the outcome of those patients who fail first-line therapy with glucocorticosteroids is poor. Preliminary reports suggested that the purine analogue pentostatin might be effective for treatment of steroid-refractory aGVHD. Here, we report on our single-center experience with pentostatin in this condition. From 2005 to 2008, a total of 24 consecutive patients, who had undergone first-line salvage treatment for steroid-refractory aGVHD of the gastrointestinal tract with pentostatin, were identified from 301 patients allografted during that period and retrospectively analyzed. Response to treatment, defined as CR or very good PR (VGPR), was observed in nine patients (38%), with a median time to response of 10 days. Although pentostatin was associated with only moderate myelosuppressive toxicity, if any, 2-year survival was only 17% with five of the nine responders dying from infection (four patients) or recurrent GVHD (one patient). We conclude that pentostatin is a moderately effective therapy for steroid-refractory aGVHD, showing response and outcome rates similar to other clinically used regimens.